Commentary on evidence in support of a grief‐related condition as a DSM diagnosis. Issue 1 (9th January 2020) - Simon, Naomi M.; Shear, M. Katherine; Reynolds, Charles F.; Cozza, Stephen J.; Mauro, Christine; Zisook, Sidney; Skritskaya, Natalia; Robinaugh, Donald J.; Malgaroli, Matteo; Spandorfer, Julia; Lebowitz, Barry
Abstract: The death of a loved one is one of life's greatest stressors. Most bereaved individuals experience a period of acute grief that diminishes in intensity as they adapt to the changes brought about by their loss. Over the past four decades, a growing body of research has focused on a form of prolonged grief that is painful and impairing. There is a substantial and growing evidence base that supports the validity and significance of a grief‐related disorder, including the clinical value of being able to diagnose it and provide effective targeted treatment. ICD‐11 will include a new diagnosis of prolonged grief disorder (PGD). DSM‐5 called this condition persistent complex bereavement disorder (PCBD) and included it in Section III, signaling agreement that a diagnosis is warranted while further research is needed to determine the optimal criteria. Given the remaining uncertainties, reading this literature can be confusing. There is inconsistency in naming the condition (including complicated grief as well as PGD and PCBD) and lack of uniformity in identifying it, with respect to the optimal threshold and timeframe for distinguishing it from normal grief. As an introductory commentary for this Depression and Anxiety special edition on this form of grief, the authors discuss the history, commonalities, and key areas of variability in identifying this condition. We review the state of diagnostic criteria for DSM‐5 and the current ICD‐11 diagnostic guideline, highlighting the clinical relevance of making this diagnosis.